Kualitas Konten Promosi Instagram @Atedoz.Photobooth terhadap Minat Beli Pelanggan Cabang Malabar - Nabila Cikawati; Hudi Santoso; Enden Darjatul Ulya; Rici Tri Harpin Pranata (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2026)
This study examines how the quality of promotional content on the Instagram account @atedoz.photobooth influences customer purchase intention at the Malabar branch. The research was motivated by the increasing role of social media content in shaping consumer decision-making, particularly in visually driven industries such as photobooth services. Using a quantitative explanatory approach, data were collected from 96 customers through online and offline surveys. The instrument’s validity and reliability were confirmed using Spearman’s Rho and Cronbach’s Alpha, with all items meeting the required standards. The data were further analyzed through descriptive statistics, a normality test using the Kolmogorov Smirnov method, and a correlation test applying Spearman’s Rank. The results indicate that all dimensions of content quality informativeness, relevance, visual appeal, and interactivity were perceived as high by respondents. The study also found a strong and significant positive correlation between content quality and purchase intention (? = 0.772; sig. 0.000). These findings demonstrate that well-designed promotional content on Instagram plays a meaningful role in enhancing transactional, referential, preferential, and exploratory interest among customers. The outcomes reinforce the importance of maintaining high-quality digital content as part of an effective promotional strategy.